Innovations in Health Administration Strategies for Effective Healthcare Management and Patient Care - Faiz Abdullah Alasuad Alenezi; Jayiz Faleh Aziz Alenezi; Anwar Matar N Alanazi; Mohammed Mossa Nassar Alanazi; Amira Abdullh Awad Alanazi Specialist; Thuwaini Khalaf Alanazi; Rasha Ahmad Abdullah Almaghrabi; Wafa Mohammad Awadh Alenezi; Abed Ayed Barak Al-Gathami; Majed Tanadhub M Alnefaie (International Journal of Medical Toxicology and Legal Medicine, 2024)
A critical aspect of healthcare quality is the patient experience, although healthcare administrators face difficulties in improving it within a swiftly changing landscape (Lunn et al., 2021). The 2010 Patient Protection and Affordable Care Act (ACA) significantly altered healthcare reimbursements by connecting hospital payments to patient satisfaction measures[1]. Additionally, the CMS implemented hospital value-based purchasing (VBP) programs to reward providers based on care quality and patient outcomes[2]. This change signifies a shift from primarily focusing on clinical results to incorporating patient experience as a crucial performance indicator[3]. Globally, patient experience is now considered a key measure of quality care[4]. Current studies indicate that 95% of U.S. survey participants view patient experience as extremely or very important[5].